2006
DOI: 10.1007/s10865-005-9029-0
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing and Measuring Ethnic Discrimination in Health Research

Abstract: This paper presents the General Ethnic Discrimination Scale, an 18-item measure of perceived ethnic discrimination that can be used in health research with any ethnic group. The 1569 participants (half college students, half community adults) completed the General Ethnic Discrimination scale and measures of cigarette smoking and of psychiatric symptoms. Results revealed that the General Ethnic Discrimination subscales model the latent construct of perceived ethnic discrimination equally well for Blacks, Latino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
342
3
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(372 citation statements)
references
References 71 publications
17
342
3
3
Order By: Relevance
“…Previous studies support these differences, despite the wide range of rates reported. 4,5,[43][44][45] However, caution must be used when comparing racism prevalence across studies that use different measures and response metrics. For example, our prevalence rates for health care racism are similar to studies with comparable administration modes, questions, and samples.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies support these differences, despite the wide range of rates reported. 4,5,[43][44][45] However, caution must be used when comparing racism prevalence across studies that use different measures and response metrics. For example, our prevalence rates for health care racism are similar to studies with comparable administration modes, questions, and samples.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Krieger's items were recently shown to be reliable and significantly associated with psychological distress in African Americans, Latinos, and Whites (Krieger, Smith, Naishadham, Hartman, & Barbeau, 2005). Her measure also has good convergent validity, based on its association with scores on the Schedule of Racist Events (Klonoff & Landrine, 1999), a validated instrument for African Americans that was generalized to apply across ethnic groups and then validated in African Americans, Whites, Latinos, and Asian Americans (Landrine, Klonoff, Corral, Fernandez, & Roesch, 2006). Birth Outcomes-Research nurses collected birth outcome data from medical charts.…”
Section: Pregnancy-related Stressmentioning
confidence: 99%
“…Consistent with the theory of social disorganization, ecological factors, such as drug trafficking, gangs and less neighborhood cohesion, may impact adolescents through a lack of community norms against drug use (Pantin et al, 2003) or the absence of informal social controls (Newcomb & Felix-Ortiz, 1992). Furthermore, paternal drug abuse/HIV, as well as membership in a racial/ethnic minority group, may increase the youth's (perceived) discrimination (Roth et al, 1994), which has also been associated with adolescent substance use (Landrine et al, 2006;Vakalahi, 2001). …”
Section: Discussionmentioning
confidence: 99%